4-Acetylantroquinonol B from antrodia cinnamomea enhances immune function of dendritic cells against liver cancer stem cells - Ting-Yi Li (Biomedicine & Pharmacotherapy, 2019)
The functions of 4-acetylantroquinonol B (4-AAQB), a ubiquinone derivative isolated from the mycelium of Antrodia cinnamomea, in immunotherapy for liver cancer were investigated. We found that 4-AAQB could inhibit liver cancer stem cell related manifestations and activate the antitumor ability of dendritic cells. Specifically, 4-AAQB can inhibit EpCAM, AFP and related pathways of HepG2 cells. It also significantly decreases the expression of β-catenin, inhibits the tumorigenicity and decreases the secretion of immune escape related cytokines. Moreover, 4-AAQB can stimulate the proliferation of immune cells and promote the endocytosis of immature dendritic cells. When co-cultured immature dendritic cells with EpCAM+ HepG2 cells, 4-AAQB enhanced the expression of MHC class I and II on the surface of liver cancer stem cells and dendritic cells, increased the expression of costimulatory molecules CD80 of dendritic cells and cytokines related to immune activation. In conclusion, 4-AAQB from Antrodia cinnamomea can enhance immune function of dendritic cells against liver cancer stem cells, and may have the potential to be used for liver cancer prevention and immunotherapy.